Morphological traits and microbiome diversity in the free-living nematodes Acrobeles complexus and Zeldia punctata - Ebrahim Shokoohi; Peter Masoko (PLoS ONE, 2026)
Morphological adaptations play a key role in shaping the feeding behavior and microbiome associations of Cephalobidae nematodes. To investigate how morphology influences nematode-associated microbiomes, we selected two widely distributed species: Acrobeles complexus , exhibiting elaborated oral structures, and Zeldia punctata , with simpler oral morphology. Unlike earlier studies that reported the microbiomes of A. complexus and Z. punctata independently, this study is the first to directly compare the two species. By integrating in silico re-analysis of our previously published microbiome datasets with new light microscopy and scanning electron microscopy (SEM) observations, we demonstrate how morphological adaptations, such as labial probolae and cuticle structures, shape associated bacterial communities. Our results revealed that A. complexus harbored a more diverse bacterial community than Z. punctata . Morphology showed that the complex oral structures of A. complexus facilitated selective bacterial capture, supporting greater microbial diversity compared to the simpler morphology of Z. punctata . Although statistical significance was not observed, the two species showed distinct patterns of microbial richness and diversity. Principal Coordinate Analysis (PCoA) revealed clearly separated bacterial community structures between the species. Linear discriminant analysis effect size identified potential microbial biomarkers at the genus level, including Firmicutes and Clostridium in A. complexus and Actinobacteria and Pseudomonas in Z. punctata . Predicted functional pathway analysis revealed notable differences in microbial metabolism, such as enrichment of bacterial secretion systems in A. complexus and amoebiasis and lipid metabolism pathways in Z. punctata . This study highlights the role of morphological adaptations in shaping microbiome composition in Cephalobidae nematodes and provides insights into the contribution of free-living bacterivorous nematodes to soil microbial balance. These findings lay the groundwork for further studies on nematode-mediated microbial interactions in soil ecosystems.